PERFORMANCE ANALYSIS OF OFFICERS IN FIRE EXTINGUISHING SERVICES AT THE FIRE FIGHTING DEPARTMENT IN LANGKAT REGENCY (International Journal of Cultural and Social Science, 2026)
Fire is a disaster that can cause significant losses, both in terms of material and human loss. The Langkat Regency Fire Department plays a primary role in providing firefighting services and rescuing affected communities. The performance of firefighters is a determining factor in the effectiveness and efficiency of the services provided. This paper will examine the performance of firefighters in Langkat Regency in firefighting services and the factors that hinder their performance. The research method used is a qualitative approach. Research informants were individuals who provided information about the situation and conditions underlying the research. Informants are individuals who are fully familiar with the issues being studied. The results of the study indicate that the performance of firefighters in Langkat Regency has generally performed well and meets the dimensions of public service quality. Although there are limitations in terms of physical facilities that require improvement, in terms of reliability, responsiveness, assurance, and concern, the service demonstrates positive and professional quality. Furthermore, there are obstacles encompassing internal and external factors.